Jawabanmu

Jawaban paling cerdas!
2014-05-31T15:41:48+07:00
Yang nomor 1 caranya :
a/b + (a+10b)/(b+10a) = 2 diubah menjadi a/b + (a/b + 10)/(1 + 10a/b) =2
misalkan a/b = x
maka x + (x + 10)/(1 + 10x) = 2 ------> (x + 10)/(1 + 10x) = 2 - x
x + 10 = 2 - 10x^2  + 19x
(5x -4) (x - 1) = 0 -----> x = 4/5 atau 1
jawabanynya a/b = 4/5 atau 0,8 (gk ada jawabannya)
kalo nomer dua caranya (a^2 + a^-2)^3 = 4^3
hasilnya a^6 + a^-6 + 3a^2 + 3a^-2 = 64 a^6 + a^-6 + 3(a^2 + a^-2 ) = 64 ---------> a^6 + a^-6 + 3(4) = 64 a^6 + a^-6 + 12 = 64 ------> a^6 + a^-6 = 52